Heat sink and semiconductor package

JP7630771B2Active Publication Date: 2025-02-18SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021142664
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-02
Filing Date
2021-09-01
Publication Date
2025-02-18
Estimated Expiration
2041-09-01

AI Technical Summary

Benefits of technology

【0008】 本開示の放熱板によれば、熱伝導率と線膨張係数のバランスがよく、放熱性能に優れた放熱板を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630771000008
    Figure 0007630771000008
  • Figure 0007630771000009
    Figure 0007630771000009
  • Figure 0007630771000010
    Figure 0007630771000010
Patent Text Reader

Abstract

To provide a heat sink and a semiconductor package having a good balance between thermal conductivity and coefficient of linear expansion and excellent heat dissipation performance.SOLUTION: A heat sink 1 having a structure in which three or more layers are laminated includes a first layer 101 that is at least one of the two outermost layers in the thickness direction of the laminated structure. The first layer 101 is composed of a first material 10. The first material 10 is a material containing an additive phase mainly composed of graphite in a metal phase mainly composed of copper, and the volume ratio of the additive phase to the entire first material 10 is 3 volume% or more and 16 volume% or less, the thickness of the first layer 101 is more than 0.1 mm and less than 0.35 mm, and a value obtained by subtracting the thermal conductivity in the thickness direction of the first layer 101 from the thermal conductivity in the plane direction orthogonal to the thickness direction of the first layer 101 is 60 W / m K or more.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a heat sink and a semiconductor package. [Background technology]

[0002] In the semiconductor field, heat sinks are used to efficiently diffuse heat generated from semiconductor elements to prevent overheating of the semiconductor elements. Metals such as copper, which have high thermal conductivity, have been used as heat sinks. Due to the difference in linear expansion coefficient between the metal heat sink and the semiconductor element or ceramic package, thermal stress occurs at the interface between them, which may cause damage to the semiconductor element. For this reason, composite materials of metals with high thermal conductivity and metals with low linear expansion coefficients are used as heat sinks. For example, Patent Document 1 discloses a heat sink in which copper (Cu) layers and molybdenum copper (Mo-Cu) composite layers are alternately laminated, with the outermost layer being a copper layer. It is said that a heat sink with excellent thermal conductivity in the plate thickness direction and low thermal expansion coefficient can be obtained by thinning the copper layer of the outermost laminated layer. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-096654 A Summary of the Invention [Problem to be solved by the invention]

[0004] According to the structure described in Patent Document 1, heat generated from a semiconductor element arranged in contact with the center of the surface is easily transmitted in the thickness direction of the heat sink, and thermal expansion in the planar direction of the heat sink can be reduced. However, with the advancement of semiconductor technology, there is a tendency for heat generated from semiconductor elements to be greater than ever before. There is a demand for a heat sink that has higher heat dissipation performance than ever before and is less susceptible to damage due to thermal stress. The present disclosure aims to provide a heat sink that has a good balance between thermal conductivity and linear expansion coefficient and has even better heat dissipation performance than before. [Means for solving the problem]

[0005] The heat sink disclosed herein has a structure in which three or more layers are laminated, and includes a first layer which is at least one of both outermost layers in a thickness direction of the laminated structure, the first layer being made of a first material, the first material being a material containing an additive phase mainly composed of graphite in a metal phase mainly composed of copper, the volume ratio of the additive phase to the entire first material being 3 volume % or more and 16 volume % or less, the thickness of the first layer being more than 0.1 mm and less than 0.35 mm, and a value obtained by subtracting the thermal conductivity of the first layer in the thickness direction from the thermal conductivity in a plane direction perpendicular to the thickness direction of the first layer is 60 W / m·K or more.

[0006] The heat sink of the present disclosure has a structure in which three or more layers are stacked, and includes a first layer which is at least one of the two outermost layers in the thickness direction of the stacked structure, and the thickness of the first layer is greater than 0.1 mm and less than 0.35 mm, the first layer is made of a first material, and the first material is a material containing an additive phase mainly composed of graphite in a metal phase mainly composed of copper, and the volume ratio of the additive phase to the entire first material is 3 volume % or more and 16 volume % or less, the additive phase is dispersed in the metal phase as a plurality of particles, each of the plurality of particles has an anisotropic shape having a longitudinal direction, and the number of the particles in which the angle between the longitudinal direction and a plane direction perpendicular to the thickness direction of the first layer is 20 degrees or less accounts for 66% or more of the total number of the plurality of particles.

[0007] The semiconductor package of the present disclosure includes the above-mentioned heat sink and a semiconductor element disposed on the surface of the first layer. Effect of the Invention

[0008] According to the heat sink of the present disclosure, a heat sink having a good balance between thermal conductivity and linear expansion coefficient and excellent heat dissipation performance can be obtained. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a perspective view showing an example of a heat sink according to an embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view illustrating the AA cross section of the heat sink of FIG. [Diagram 3] FIG. 3 is an enlarged schematic cross-sectional view of region B in FIG. [Figure 4] FIG. 4 is a diagram illustrating the inclination of graphite. [Figure 5A] FIG. 5A is a schematic cross-sectional view showing an example of three layers of a heat sink according to an embodiment. [Figure 5B] FIG. 5B is a schematic cross-sectional view showing an example of seven layers of a heat sink according to an embodiment. [Figure 5C] FIG. 5C is a schematic cross-sectional view showing an example of four layers of a heat sink according to an embodiment. [Figure 5D] FIG. 5D is a schematic cross-sectional view showing another example of three layers of the heat sink according to the embodiment. [Figure 6] FIG. 6 is a diagram illustrating an example of a configuration of a semiconductor package. [Figure 7] FIG. 7 is a diagram for explaining the procedure for preparing a sample for measuring thermal conductivity in the planar direction. [Figure 8] FIG. 8 is a diagram for explaining the procedure for preparing a sample for measuring thermal conductivity in the thickness direction. [Figure 9] FIG. 9 is a diagram illustrating a method for evaluating the heat dissipation performance of the laminate. [Figure 10] FIG. 10 is a cross-sectional photograph of a heat sink according to the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Description of the embodiments of the present disclosure] In the conventional technology for improving the thermal conduction in the thickness direction of the heat sink, the heat transmitted from the heat generating body to the heat sink is transmitted isotropically in the thickness direction and the planar direction of the heat sink. Therefore, in the thin surface layer, the heat on the surface is transmitted to the back side before spreading in the planar direction. In other words, the heat flow is concentrated in the plate thickness direction directly under the heat source. The inventor of the present application focused on such heat flow and found a problem that the effect of heat conduction in the plate thickness direction is difficult to obtain in the peripheral part of the heat sink where the heat generating body is not in contact. In particular, when the total surface area of ​​the heat sink is larger than the area of ​​the part where the heat generating body is in contact with the heat sink, the part where the heat generating body is not in contact is difficult to contribute to heat dissipation, and the performance of the heat sink cannot be fully demonstrated.

[0011] The embodiments of the present disclosure are listed and described below. (1) A heat sink according to an embodiment of the present disclosure has a structure in which three or more layers are laminated. The heat sink includes a first layer that is at least one of the two outermost layers in the thickness direction of the laminated structure, and the first layer is made of a first material. The first material is a material containing an additive phase mainly composed of graphite in a metal phase mainly composed of copper. The volume ratio of the additive phase to the entire first material is 3 volume % or more and 16 volume % or less. The thickness of the first layer is more than 0.1 mm and less than 0.35 mm. A value obtained by subtracting the thermal conductivity of the first layer in the thickness direction from the thermal conductivity of the first layer in the plane direction perpendicular to the thickness direction is 60 W / m·K or more. The thickness direction of the laminated structure is the direction in which the three or more layers are laminated, and the plane direction is the direction perpendicular to the thickness direction.

[0012] By adding graphite to the outermost layer, which is the surface layer that comes into contact with the heating element, it is possible to change the thermal conductivity compared to when copper alone is used. Here, by creating a difference between the thermal conductivity in the thickness direction and the thermal conductivity in the surface direction of the first layer, and making it easier for heat to be transmitted in the surface direction than in the thickness direction, thermal conduction over the entire surface is more likely to contribute to heat dissipation. By spreading heat in the surface direction in the first layer, which has the surface that comes into contact with the heating element, heat is more easily transmitted in the thickness direction over the entire surface. This makes it possible to obtain a heat sink with a good balance between thermal conductivity and linear expansion coefficient, and excellent heat dissipation performance.

[0013] (2) A heat sink according to another embodiment of the present disclosure is a heat sink having a structure in which three or more layers are laminated. The heat sink includes a first layer which is at least one of the two outermost layers in the thickness direction of the laminated structure. The thickness of the first layer is more than 0.1 mm and less than 0.35 mm. The first layer is made of a first material. The first material is a material containing an additive phase mainly composed of graphite in a metal phase mainly composed of copper. The volume ratio of the additive phase to the entire first material is 3 volume % or more and 16 volume % or less. The additive phase is dispersed as a plurality of particles in the metal phase. Each of the plurality of particles has an anisotropic shape having a longitudinal direction. The number of the particles in which the angle between the longitudinal direction and a plane direction perpendicular to the thickness direction of the first layer is 20 degrees or less is 66% or more of the total number of the plurality of particles.

[0014] By adding graphite to the outermost layer, which is the surface layer that comes into contact with the heating element, the thermal conductivity can be changed compared to when copper alone is used. Here, it is preferable for the shape of the graphite particles to be anisotropic. By bringing the longitudinal direction of the anisotropic particles closer to the surface direction of the first layer, the thermal conductivity in the surface direction can be made higher than the thermal conductivity in the thickness direction. By making it easier for heat to be transmitted in the surface direction, the thermal conduction over the entire surface can more easily contribute to heat dissipation. This makes it possible to obtain a heat sink with a good balance between thermal conductivity and linear expansion coefficient and excellent heat dissipation performance.

[0015] (3) In one aspect of the above embodiment, the first layer may have a thermal conductivity in the thickness direction of 300 W / m·K or more, and a linear expansion coefficient of the first layer in the planar direction when the temperature changes from room temperature to 300° C. may be 17.5 ppm / K or less.

[0016] In order to obtain high heat dissipation performance of the entire heat sink, it is preferable that the thermal conductivity in the thickness direction of the first layer is high. In addition, in consideration of use at high temperatures, it is preferable that the linear expansion coefficient in the plane direction is equal to or less than a certain value. According to the configuration of the above embodiment (3), it is possible to obtain a heat sink having a good balance between the thermal conductivity in the thickness direction and the linear expansion coefficient in the plane direction, and excellent heat dissipation performance.

[0017] (4) One aspect of the above embodiment may include a second layer in contact with the first layer, wherein the second layer has a thermal conductivity in the thickness direction of 140 W / m K or more, and a linear expansion coefficient in the plane direction of the second layer when the temperature is changed from room temperature to 300° C. is 8.0 ppm / K or less.

[0018] The second layer is provided for the purpose of lowering the linear expansion coefficient in the planar direction of the entire heat sink. When the second layer has the above-mentioned configuration, a heat sink having a good balance between thermal conductivity and linear expansion coefficient and excellent heat dissipation performance can be obtained.

[0019] (5) In one aspect of the above embodiment, the second layer may be made of a second material including molybdenum or tungsten.

[0020] Molybdenum and tungsten are suitable materials for adjusting the thermal conductivity and linear expansion coefficient of the second layer. Molybdenum or tungsten may be used alone for the second layer. The desired performance can also be obtained by using a material that combines molybdenum or tungsten with copper. This allows for a well-balanced thermal conductivity in the thickness direction and linear expansion coefficient in the surface direction to be obtained, resulting in a heat sink with excellent heat dissipation performance.

[0021] (6) In the case where the above embodiment is a heat sink having three laminated layers, both of the outermost layers may be the first layer, and the layer between the outermost layers may be the second layer.

[0022] Laminating the first layer, the second layer, and the first layer in this order is a preferred combination when the number of layers is three. This three-layer structure provides a good balance between the thermal conductivity in the thickness direction and the linear expansion coefficient in the surface direction, resulting in a heat sink with excellent heat dissipation performance. In addition, by making the layer structure symmetrical in the lamination direction, the heat sink itself is less likely to warp.

[0023] (7) In the above embodiment, when the heat sink is formed by stacking an odd number of layers, five or more, both of the outermost layers are the first layer, a pair of layers in contact with each of the outermost layers are the second layer, and a third layer in contact with a surface of the pair of second layers opposite to the surface in contact with the first layer is preferably composed of copper or a copper alloy.

[0024] When the five-layer laminate is used as a heat sink, it is preferable to laminate the layers in the order of the first layer, the second layer, the third layer, the second layer, and the first layer. Here, the third layer is a layer for obtaining mainly thermal conduction performance, and is preferably composed of a material mainly composed of copper. The third layer is preferably copper or a copper alloy. The third layer may be made of the same material as the first layer. In addition, pure copper made of copper and unavoidable impurities is also preferably used for the third layer. This five-layer structure makes it possible to obtain a heat sink with a good balance between the thermal conductivity in the thickness direction and the linear expansion coefficient in the surface direction, and excellent heat dissipation performance.

[0025] (8) A semiconductor package according to an embodiment of the present disclosure includes any one of the heat sinks described above and a semiconductor element disposed on a surface of the first layer.

[0026] By using the above-mentioned heat sink having excellent heat dissipation performance, it is possible to obtain a semiconductor package which prevents malfunction or damage caused by overheating of the semiconductor element.

[0027] [Details of the embodiment of the present disclosure] Hereinafter, specific examples of heat sinks according to embodiments of the present disclosure will be described with reference to the drawings. The same reference numerals in the drawings indicate the same or corresponding parts. The sizes and positional relationships of the members shown in each drawing are expressed for the purpose of clarifying the description, and do not necessarily represent the actual dimensional relationships. The configuration described in one embodiment can be applied to other embodiments unless otherwise specified. In the following description, terms indicating specific directions or positions are used, but the use of these terms is for the purpose of facilitating understanding of the invention with reference to the drawings, and the meaning of these terms does not limit the technical scope of the present invention. Examples of terms indicating specific directions or positions include "top," "top surface," "front," and "front."

[0028] FIG. 1 is a perspective view showing an example of a heat sink according to an embodiment. The heat sink 1 in FIG. 1 has a front surface 2 and a back surface 3, and is a plate-like body that is rectangular in plan view. In the following description, the direction of the surfaces constituting the front surface 2 and the back surface 3 of the heat sink 1 is defined as the XY plane, and the thickness direction of the plate is defined as the Z direction. A heating element (not shown) that is the target of heat dissipation is arranged on a part or all of the front surface 2. Heat transferred from the heating element to the front surface 2 is transferred in the thickness direction, i.e., the Z direction, and is dissipated from the back surface 3. The back surface 3 may be in contact with a metal or liquid as another heat transfer medium. The heat sink 1 has a structure in which multiple layers are stacked in the Z direction, with one surface of the outermost layer exposed as the front surface 2 and one surface of the other outermost layer exposed as the back surface 3.

[0029] FIG. 2 is a schematic diagram illustrating a cross section of the heat sink 1 of FIG. 1 cut in the Z direction along the line AA. The heat sink 1 has a plurality of layers in the Z direction. In this embodiment, the case of five layers is shown. Hereinafter, for convenience of explanation, the layers having the front surface 2 arranged at the top of the figure are called the first layer 101, the second layer 102, the third layer 103, the fourth layer 104, and the fifth layer 105 in that order. The first layer 101 is made of the first material 10. The second layer 102 in contact with the first layer 101 is made of the second material 20. The third layer 103 is made of the third material 30. The fourth layer 104 is made of the same second material 20 as the second layer 102. The fifth layer 105 having the back surface 3 is made of the first material 10. The thickness of each layer can be selected arbitrarily. In the embodiment shown in FIG. 2, the first layer 101 and the fifth layer 105, and the second layer 102 and the fourth layer 104 have the same thickness. As a result, the heat sink 1 of this embodiment has a laminated structure that is symmetrical above and below the center in the thickness direction.

[0030] The first material 10 is a material containing an additive phase mainly made of graphite in a metal phase mainly made of copper. Here, the "metal phase mainly made of copper" refers to a metal phase in which the copper content in the metal phase is 50 mass percent or more. The metal phase mainly made of copper preferably contains 70 mass percent or more of copper, and is most preferably pure copper. Pure copper is a metal material made of copper and unavoidable impurities. Graphene is included in graphite. "Mainly made of graphite" does not exclude the inclusion of impurities, and may contain impurities in natural graphite or unavoidable impurities contained in the production process.

[0031] By using such a material, it is possible to make the value obtained by subtracting the thermal conductivity in the thickness direction from the thermal conductivity in the plane direction of the first layer 101 60 W / m·K or more. Since the thermal conductivity in the plane direction is higher than the thermal conductivity in the thickness direction, heat is easily transferred in the plane direction. For example, heat transferred to a part of the surface 2 of the first layer 101 is transferred in the plane direction and the thickness direction in the first layer 101. Therefore, the entire first layer 101 can contribute to heat conduction in the thickness direction. Heat transferred from the surface 2 of the first layer 101 to the surface in contact with the second layer 102 is then transferred in the thickness direction from the second layer 102. Therefore, the heat sink 1 as a whole can efficiently transfer heat in the thickness direction.

[0032] Fig. 3 shows the state in which the additive phase exists in the metal phase. Fig. 3 is a schematic diagram showing an enlarged cross section of region B shown by the dashed line in Fig. 2. The additive phase 12, which is graphite, is dispersed as multiple particles in the metal phase 11. The shape of the particles of the additive phase 12 is not uniform. The individual particles may be separated from each other, or multiple particles may be in contact with each other.

[0033] The shape of the particles of the additive phase 12 has a certain anisotropy. Here, anisotropy means that the shape of the particles is not isotropic like a cube or a sphere. Because of the anisotropy, the longitudinal direction can be defined in the cross section of each particle. Below, the longitudinal direction of the particles of the additive phase 12, its inclination, and the orientation rate will be explained.

[0034] FIG. 4 shows one of the particles of the additive phase 12 in the cross section of the first layer 101 shown in FIG. 3 in the thickness direction. In the cross-sectional shape of the particle, two parallel line segments are drawn that are in contact with the outer periphery of the particle, and the widths L1 and L2 of the line segments in two perpendicular directions are obtained. Here, L1 is determined so that the value of L1 / L2, which is the ratio of L1 to L2, is maximized. The direction of L1 in this case is the longitudinal direction of the particle. The angle θ between the longitudinal direction of the particle and the XY plane, which is the horizontal axis of FIG. 4, that is, the angle that the particle makes with the plane parallel to the surface, is obtained. The angle is defined as the angle measured on the acute angle side between the line segment projected from the Z direction of the longitudinal direction of the particle onto the XY plane and the longitudinal direction.

[0035] Regarding the angles θ of a plurality of particles found within the field of view to be observed, the ratio of the number of particles whose angle θ falls within a certain range is expressed as a percentage and defined as the orientation rate of the entire added phase 12 in the first layer 101. For example, if the angle θ is set to 20 degrees or less, when the orientation rate of angles 20 degrees or less is high, most of the particles are inclined in a direction close to the XY plane.

[0036] The second material 20 is a material containing molybdenum or tungsten. It is preferable to use a material having a smaller linear expansion coefficient than the first layer 101 for the second layer 102. By reducing the linear expansion coefficient of the second layer 102, the linear expansion coefficient in the planar direction of the entire heat sink 1 can be reduced. As the material containing molybdenum or tungsten, a known material used for the heat sink 1 can be applied. For example, the material constituting the second layer 102 may be a material made of molybdenum or tungsten and unavoidable impurities. The material constituting the second layer 102 is preferably a composite material in which copper is impregnated into a porous body obtained by sintering molybdenum or tungsten powder. By using a composite material, the thermal conductivity and linear expansion coefficient can be adjusted to a desired range. The material containing molybdenum or tungsten may be any of a material containing molybdenum, a material containing tungsten, and a material containing both molybdenum and tungsten.

[0037] The third material 30 is preferably a material containing copper as a main component, but is not particularly limited to this. The same material as the first material 10 can be used as the third material 30. By using a material with good thermal conductivity for the third layer 103, it is possible to increase the thermal conductivity of the entire heat sink 1 in the thickness direction. Pure copper is preferably used as the third material 30.

[0038] Although the above description has been given with an example of the heat sink 1 having five layers, the number of layers may be three or more. An example of the heat sink 1 having three layers is shown in FIG. 5A. In the case of three layers, the third layer 103 and the fourth layer 104 shown in FIG. 2 do not exist. The heat sink 1 in FIG. 5A is composed of the first material 10, the second material 20, and the first material 10 in this order from the front surface 2 to the back surface 3. In the case of seven layers or more, it is preferable to increase the number of repetitions of the third material 30 and the second material 20. FIG. 5B shows a typical structure in the case of seven layers. The heat sink 1 in FIG. 5B is composed of the first material 10, the second material 20, the third material 30, the second material 20, the third material 30, the second material 20, and the first material 10 in this order from the front surface 2 to the back surface 3.

[0039] In the embodiment of the present disclosure, regardless of the number of layers, the first layer 101 having the surface 2 is made of the first material 10. The surface 2 is a surface that contacts a heat generating body to be dissipated, and the heat sink 1 transfers heat from the surface 2 to the back surface 3. When the number of layers is odd, the surface 2 and the back surface 3 are preferably made of the same first material 10. The number of layers can also be an even number. In this case, there is no particular limitation other than that the surface 2 is made of the first material 10 and the second layer 102 is made of the second material 20. FIG. 5C shows an example of a four-layer configuration as an example of a case where the number of layers is even. The heat sink 1 in FIG. 5C is made of the first material 10, the second material 20, the third material 30, and the second material 20 in this order from the surface 2 to the back surface 3.

[0040] Various modifications of the structure described above are possible, and are not limited to the above configuration. For example, another configuration example of the heat sink 1 in the case of three layers is shown in Fig. 5D. The heat sink 1 shown in Fig. 5D has a first layer 101 having a front surface 2 made of a first material 10, a second layer 102, which is the second layer from the front surface 2, made of a second material 20, and a material having a back surface 3 made of a third material 30.

[0041] (Semiconductor Package) FIG. 6 is a diagram illustrating an example of a semiconductor package 50 including a heat sink 1 according to the present disclosure. A semiconductor element 53 is disposed on the front surface 2 of the heat sink 1. A current is supplied to the semiconductor element 53 via a terminal 51. A case member 52 for sealing the semiconductor element 53 is provided on the front surface 2 of the heat sink 1. The function of the heat sink 1 is to quickly transfer heat generated from the semiconductor element 53 to the outside and maintain the temperature of the semiconductor element 53. For this reason, the back surface of the heat sink 1 is used in contact with a metal plate or other cooling medium (not shown). The heat sink 1 according to the present disclosure easily transfers heat generated from the semiconductor element 53 in the surface direction in the first layer constituting the front surface 2. The heat that spreads in the surface direction is transferred in the thickness direction through the entire heat sink 1. Furthermore, the linear expansion coefficient in the surface direction of the heat sink 1 is close to that of materials such as ceramics used for the semiconductor element 53 and the case member 52, so that each material and the joint surface are unlikely to be damaged by temperature changes. Compared to the case where a conventional heat sink is used, heat from the semiconductor element 53 is more easily transferred to the back surface, and the semiconductor package 50 can have both high cooling performance and durability. The configuration of the semiconductor package 50 is not limited to the above example, and there are many types of configurations. Regardless of the difference in configuration, the semiconductor package 50 of the present disclosure includes a structure in which the semiconductor element 53 is disposed so that heat from the semiconductor element 53 is transferred to the front surface 2 of the heat sink 1 of the present disclosure, and the heat is transferred to the back surface of the heat sink 1 to obtain a cooling effect.

[0042] Example A (Manufacture of heat sinks) A five-layer heat sink as shown in FIG. 2 was fabricated as follows.

[0043] (Preparation of the first ingredient) Spherical copper (Cu) powder with an average particle size of 50 μm (Cu-At-100 manufactured by Fukuda Metal Foil Powder Co., Ltd.) and graphite (Gr) particles with anisotropy having a thickness of 10 μm or less and a long axis of 40 μm or more (UP-35N manufactured by Nippon Graphite Industries Co., Ltd.) were mixed in a volume ratio of 100:0 to 82.7:17.3. The graphite particles used had an average long axis length of 45 μm and an average thickness of 3.5 μm. The mixed powder was loaded into a carbon mold with a diameter of 30 mm, and then heated at a temperature of 950° C. for 10 minutes while applying a pressure of 30 MPa in an electric plasma sintering device to obtain a sintered body. Note that only in Experimental Example A10 described later, graphite particles with an average long axis length of 25 μm were used for comparison.

[0044] (Preparation of the second ingredient) Molybdenum (Mo) plates of a specified thickness were prepared for use as the second and fourth layers.

[0045] (Preparation of the third ingredient) A pure copper plate of a specified thickness was prepared for use as the third layer.

[0046] (Manufacture of laminates) The first material, the second material, and the third material prepared as described above were each processed into a disk shape with a diameter of 30 mm. The disk-shaped materials were stacked in the order of the first material, the second material, the third material, the second material, and the first material, and loaded into a graphite mold with an inner diameter of 32 mm. The filled stacked sample was bonded by hot pressing under the conditions of a temperature of 1000°C, a time of 60 minutes, and a pressure of 50 MPa. The overall thickness after hot pressing was set to 1 mm. In the hot pressing, the copper powder contained in the first material is deformed into a flat shape following the direction of the press. The graphite particles having anisotropy are arranged so as to follow the flat shape of the copper powder, so that the graphite particles in the first material have an orientation. Note that the thickness of the first material is reduced by hot pressing depending on the filling rate of the copper powder, so the thickness is adjusted in advance so that the desired thickness is obtained after hot pressing. In this experimental example, the manufacturing was performed only by hot pressing, but it can also be manufactured by rolling.

[0047] (evaluation) The thermal conductivity in the plane direction and thickness direction, and the linear expansion coefficient in the plane direction were measured for the materials of each layer before lamination and for the joined laminate.

[0048] (Measurement sample for measuring thermal conductivity in the planar direction) A sample for measuring the thermal conductivity in the planar direction of the first material was prepared as follows. FIG. 7 is a diagram for explaining the procedure for preparing a sample for measuring the thermal conductivity in the planar direction. FIG. 7 shows the procedure for preparing a sample by cutting out the first material 10 from the heat sink 1. FIG. 7(a) shows the heat sink 1 to be evaluated. The heat sink 1 is a laminate. The first material 10 constituting the first layer of the laminate is cut out from the laminate. The thickness of the cut out first material is t mm. The material is cut into a thin piece with a length of A mm and a width of 2 mm as shown in FIG. 7(b). The length A is 1 mm to 10 mm, and is preferably 10 mm. In this measurement, the length A was set to 10 mm.

[0049] The following procedure will be described with reference to (c) and (d) of FIG. 7. X is the number obtained by rounding up the value obtained by dividing 10 (mm) by t (mm), and Y is the number obtained by rounding up the value obtained by dividing 10 (mm) by A (mm). The number of flakes to be prepared is the product of X and Y. X flakes are stacked to create a block with a height of about 10 mm, a length of A mm, and a width of 2 mm. Y blocks are produced. Here, as shown by Ag and the arrow in FIG. 7 (c), pure silver amorphous powder (AgC-74SE manufactured by Fukuda Metal Foil and Powder Co., Ltd.) with an average particle size of about 4 μm is placed between each of the stacked flakes. The amount of pure silver amorphous powder Ag used is 100 mm between each layer. 2The weight is set to within the range of 0.2g ±30% per block. Next, this block is placed in a rectangular graphite mold with an opening of inner dimensions A (mm) × 2 (mm). A load P of 4.9N to 9.8N is applied from above as shown by the thick arrow in Figure 7(c), and the silver powder is softened and deformed by heat treatment at 900°C for 10 minutes in inert gas to bond the silver powder. By arranging Y blocks obtained, a measurement sample with a height of approximately 10mm, length of approximately 10mm, and width of 2mm is completed (Figure 7(d)). When arranging the Y blocks, the blocks may be bonded with an adhesive material that can withstand heat up to approximately 800°C, such as silver brazing foil or ceramic adhesive. The blocks may also be fixed by wrapping the outer periphery with stainless steel wire.

[0050] (Measurement sample for measuring thermal conductivity through thickness) The measurement sample for the thermal conductivity in the thickness direction of the first material, the second material, the third material, or the laminate was prepared as follows. Figure 8 is a diagram explaining the procedure for preparing a measurement sample for the thermal conductivity in the thickness direction. Figure 8 shows the procedure for preparing a sample by cutting out the first material from the heat sink 1. Figure 8 (a) is the heat sink 1 to be evaluated. The heat sink 1 is a laminate. The first material 10 constituting the first layer of the laminate is cut out from the laminate. When the measurement target is the second material or the third material, the procedure is the same except that the cut-out target is different. The thickness of the cut-out material to be measured is t mm. The material is cut into a thin piece with a length of B mm and a width of C mm as shown in Figure 8 (b). The length B and the length C are each 1 mm to 10 mm, and are preferably 10 mm. In this measurement, the length B and the width C were both set to 10 mm.

[0051] The following procedure will be described with reference to (c) and (d) in FIG. 8. The number obtained by rounding up the value obtained by dividing 2 (mm) by t (mm) is X1, the number obtained by rounding up the value obtained by dividing 10 (mm) by B (mm) is Y1, and the number obtained by rounding up the value obtained by dividing 10 (mm) by C (mm) is Y2. The number of flakes to be prepared for the material is the product of X1, Y1, and Y2. First, X1 flakes are stacked to create a block with a height of about 2 mm, a length of B mm, and a width of C mm. The number of blocks is the product of Y1 and Y2. Here, pure silver amorphous powder Ag with an average particle size of 4 μm is placed between each of the laminated flakes as shown by Ag and the arrow in FIG. 8 (c). The amount of pure silver amorphous powder used is 100 mm between each layer. 2 The weight should be within the range of 0.2g ±30% per block. Next, this block is placed in a rectangular graphite mold with an opening of inner dimensions B (mm) × C (mm). A load P of 4.9N to 9.8N is applied from above as shown by the thick arrow in Figure 8(c) and heat treated at 900°C for 10 minutes in inert gas to soften and deform the silver powder and bond it. The obtained blocks are arranged in Y1 vertical and Y2 horizontal rows to complete a measurement sample with a height of approximately 10mm, length of approximately 10mm, and width of 2mm (Figure 8(d)). When arranging Y1 vertical and Y2 horizontal rows, the blocks may be bonded with an adhesive material that can withstand heat up to approximately 800°C, such as silver brazing foil or ceramic adhesive. The blocks may also be fixed by wrapping the outer periphery with stainless steel wire.

[0052] (Measurement of thermal conductivity) Thermal conductivity is evaluated by the laser flash method. Thermal diffusion coefficient is measured using a thermal conductivity measuring device (NETZSCH LFA457MicroFlash). Thermal conductivity at room temperature is calculated using the specific heat of the measurement sample obtained from the volume ratio of the constituent materials. The specific heat values ​​used are as follows: Cu: 386 J / (kg K) Mo: 251 J / (kg K) Ag: 234 J / (kg K) (The above is from Metal Data Book 4th Edition, Japan Institute of Metals (2004)) Gr:2.038 cal / (mol·K)(=710J / (kg·K)) (Chem. Thermodynamics, 2, 847 (1970)) In the evaluation, a pure copper sample of the same shape was used as a reference, measured under the same conditions, and numerical correction was performed.

[0053] (Measurement of linear expansion coefficient in the plane direction) The linear expansion coefficient in the in-layer direction of the first material 10 when the temperature changes from room temperature to 300°C is calculated by measuring the expansion displacement in the in-layer direction of the first material 10 when the temperature changes from room temperature to 300°C using a TD5000SA (manufactured by Bruker AXS). When calculating the linear expansion coefficient in the in-layer direction of the first material 10 when the temperature changes from room temperature to 300°C, the planar shape of the first material 10 is preferably a rectangular shape of t mm × 3 mm × (10 to 15) mm, where t is the thickness of the sample. The measured value is the average value for three samples. When the evaluation target is smaller than the above dimensions, the linear expansion coefficient may be calculated using X-ray diffraction. When the heat dissipation surface of the first material 10 has a total area of ​​100 mm 2 Rectangles with sides of 10 mm or more are accumulated on the same plane so that the surface of the accumulated sample is irradiated with X-rays at room temperature and 300°C, and the diffraction angle (2θ) is derived from the diffraction peak corresponding to Cu(331). The rate of change in lattice spacing can be used as the linear expansion coefficient by using the following formula from the diffraction angle. If anisotropy exists within the material plane, the sample is aligned so that the direction of measurement of the linear expansion coefficient of the sample is parallel to the plane of incidence of the X-rays. The formula for calculating the linear expansion coefficient when room temperature is 25°C is shown below. (Linear expansion coefficient) = (1 / sin(θat300℃)-1 / sin(θat25℃)) × sin(θat25℃) / (300-25) Here, θat25℃ is 1 / 2 the diffraction angle 2θ when measured at 25℃. θat300℃ is 1 / 2 the diffraction angle 2θ when measured at 300℃

[0054] (Evaluation of heat dissipation performance of laminate) The laminate produced above was evaluated for heat dissipation performance in the surface direction. The difference between the temperature at the center of the laminate surface and the temperature at the edge of the surface is called the edge temperature difference. The edge temperature difference was used as an index of the heat dissipation performance of the laminate and was evaluated as follows.

[0055] FIG. 9 is a diagram for explaining a method for evaluating the heat dissipation performance of a laminated heat sink. FIG. 9 is a schematic diagram showing the arrangement described below, viewed from one side of the heat sink 1. The heat sink 1 is cut into a rectangle with a length and width of 10 mm when viewed from a direction perpendicular to the surface. A heating element 60 with a length and width of 1 mm is brought into contact with the center of the surface of the heat sink 1. The output of the heating element is 50 W. An aluminum fin 70 is provided so as to be in contact with the rear surface of the heat sink 1. Silicone oil (G-751 manufactured by Shin-Etsu Chemical Co., Ltd.) is applied to the interface between the heat sink 1 and the aluminum fin 70, and the heat sink 1 and the aluminum fin 70 are bonded under a load of 9.8 N. The temperature T1 of the interface between the heating element 60 and the surface of the heat sink 1, the temperature T2 of the end portion which is the corner of the surface of the heat sink 1, and the temperature of the bonding portion between the heat sink 1 and the aluminum fin 70 are measured by a thermocouple (not shown). Air cooling of the aluminum fins 70 is controlled so that the temperature of the adhesive joint between the heat sink 1 and the aluminum fins 70 is 25°C±3°C. The ambient temperature in the measurement environment is 25°C±5°C. The end temperature difference is the temperature difference T1-T2 (°C) when 30 seconds or more have passed since the heating element 60 was brought into contact with the heat sink 1 and the temperature has reached a steady state. The measurement was performed 10 times, and the average value was used as the end temperature difference. A smaller temperature difference indicates better thermal conduction within the surface.

[0056] (Graphite Orientation Evaluation) A hot-pressed body having a diameter of 30 mm and a thickness of 0.8 mm to 2.0 mm was manufactured using the first material. The hot-pressing conditions were the same as those in the preparation process of the first material described above. The structure of the cross section perpendicular to the disk surface of the hot-pressed body was observed using an optical microscope or a scanning electron microscope with a magnification of 200 times. An example of the observed cross section is shown in FIG. 10. The vertical direction in FIG. 10 is the Z direction, which is the thickness of the layer, and the horizontal direction is the in-plane direction of the XY plane. The dark gray parts shown in FIG. 10 are graphite particles, which are the additive phase 12, and the light gray areas are the metal phase 11. In FIG. 10, it was confirmed that the graphite particles of the additive phase 12 were dispersed in the metal phase 11. The shapes of the particles were not the same, and the sizes also varied. For each particle in the entire field of view, the angle θ was determined by the following procedure.

[0057] Referring again to FIG. 4, the widths L1 and L2 of the line segments tangent to the outer circumference of the particle in two perpendicular directions in the cross-sectional shape of each particle are obtained. Here, the direction of L1 when L1 is obtained so that the value of L1 / L2 is maximized is taken as the longitudinal direction of the particle. Here, small particles with L1 of 5 μm or less when L1 / L2 is maximized are not used as evaluation objects because their contribution to the orientation is small. The angle θ between the longitudinal direction of the particle and the direction of the surface in the observed cross section is obtained. The angle θ is obtained for the particles in the entire field of view to be evaluated, and the ratio of the number of particles with θ of 20 degrees or less to the number of particles to be evaluated is calculated as the orientation rate of graphite. This calculation was performed for 10 or more points in the field of view to obtain the average orientation rate.

[0058] (Volume ratio of copper and graphite in laminate) The volume ratio of copper (Cu) and graphite (Gr) in the entire laminate was determined by dissolving copper in acid from the laminate and separating and extracting graphite. The weight ratio of copper and graphite was calculated from the change in weight before and after dissolution, and the volume ratio was calculated by converting it to a volume ratio using their respective densities. Hereinafter, the volume ratio is expressed as Vol%.

[0059] (Evaluation result: A) Measurements were performed on samples with different Gr ratios, Gr orientation rates, and thicknesses for the first material that constitutes the first layer. The thickness of the completed laminate was standardized to 1 mm. The composition and measurement results of each sample are shown in Table 1. For the first layer, the Gr ratio, Gr orientation rate, layer thickness, thermal conductivity in the plane direction and thickness direction and their difference, and linear expansion coefficient in the plane direction are shown. For the second and third layers, the layer thickness, thermal conductivity in the thickness direction, and linear expansion coefficient in the plane direction are shown, respectively. For the laminate that is the completed heat sink, the total thickness, Cu ratio (the volume ratio of copper to the total), thermal conductivity in the thickness direction, linear expansion coefficient in the plane direction, and end temperature difference are shown.

[0060] [Table 1]

[0061] The performance required for the laminate to become a heat sink is judged to be good based on the criteria that the end temperature difference is 50°C or less and the linear expansion coefficient within the layer is 8 ppm / K or less. As shown in Table 1, experimental examples A4 to A8 are judged to be good.

[0062] Experimental examples A1 and A2 are the measurement results of samples that do not contain Gr in the first layer. Since Gr is not contained, the above criteria are not met. Experimental examples A3 to A5 and Experimental examples A8 to A10 are the measurement results of samples that have the same thickness of the first layer but different Gr ratios and Gr orientation rates. Since the Gr ratio of 2.6 Vol% does not meet the criteria by a small margin, it is understood that the Gr ratio needs to be 3 Vol% or more. The Gr ratio is preferably 5 Vol% or more. Furthermore, from a comparison of Experimental examples A8 and A9, it is determined that the upper limit of the Gr ratio is 16 Vol% or less, preferably 15 Vol% or less. Furthermore, the Gr orientation rate is preferably 66% or more, taking into account Experimental examples A3 to A12.

[0063] Experimental examples A5 to A7, A11 and A12 are the measurement results for samples with the same Gr ratio and Gr orientation rate but different thicknesses. From these results, it is determined that the thickness of the first layer is suitable to be 0.15 mm or more and 0.3 mm or less.

[0064] Furthermore, the higher the copper ratio in the entire heat sink, the higher the thermal conductivity in the thickness direction, making it more preferable for the heat sink. In this respect, all of the samples judged to be preferable above have a good thermal conductivity in the thickness direction of 250 W / m K or more. Furthermore, if the copper ratio is 77 Vol% or more, the thermal conductivity in the thickness direction will be 300 W / m K or more, which is even better.

[0065] Example B A laminate was produced in the same manner as in Example A, except that a molybdenum copper (Mo-Cu) composite was used as the second material.

[0066] (Preparation of Molybdenum Copper Complex) Granular molybdenum powder (TMO-30, manufactured by A.L.M.T. Co., Ltd.) with an average particle size of 3 μm was filled into a sintering vessel to a thickness of 10 mm so that the powder was 65% by volume. This was sintered in a hydrogen atmosphere at a temperature of 1800°C for 1 hour to obtain a porous body. Molten copper was poured into this porous body to impregnate it. The impregnated material was rolled and thinned to the desired thickness of 0.1 mm to 1 mm to obtain a molybdenum copper composite.

[0067] (Evaluation result: B) As with evaluation result A, measurements were taken by preparing multiple samples with different Gr ratios, Gr orientation rates, and thicknesses of the first material that constitutes the first layer. The thickness of the completed laminate was 1 mm or 1.1 mm. The composition and measurement results of each sample are shown in Table 2. The measurement items shown in Table 2 are the same as those in Table 1.

[0068] [Table 2]

[0069] The performance required for the laminate to become a heat sink is judged to be good based on the criteria that the end temperature difference is 50°C or less and the linear expansion coefficient within the layer is 8 ppm / K or less. As shown in Table 2, Experimental Example B4 to Experimental Example B6, Experimental Example B9 and Experimental Example B10 are judged to be good.

[0070] Experimental Examples B1 and B2 are the measurement results of samples that do not contain Gr in the first layer. Since Gr is not contained, the above criteria are not met. Experimental Examples B3 to B7 are the measurement results of samples that have the same thickness of the first layer but different Gr ratios and Gr orientation rates. Since a Gr ratio of 2.5 Vol% does not meet the criteria, it is considered that a Gr ratio of 3 Vol% or more is necessary. The Gr ratio is preferably 5 Vol% or more. Furthermore, from a comparison of Experimental Examples B6 and B7, it is determined that the upper limit of the Gr ratio is 16 Vol% or less, preferably 15 Vol% or less. Furthermore, taking into account Experimental Examples B6 and B7, it is preferable that the Gr orientation rate is 66% or more.

[0071] Experimental examples B5 and B8 to B11 are the measurement results for samples with the same Gr ratio and Gr orientation rate but different thicknesses. From these results, it is determined that the thickness of the first layer of the heat sink is suitable to be 0.15 mm or more and 0.3 mm or less.

[0072] Furthermore, the higher the proportion of copper in the entire heat sink, the higher the thermal conductivity in the thickness direction, making it more preferable for the heat sink. In that respect, all of the samples judged to be preferable above had a good thermal conductivity in the thickness direction of 250 W / m K or more.

[0073] Example C A laminate was produced in the same manner as in Example A, except that a tungsten (W) plate having a thickness of 0.1 mm was used as the second material.

[0074] (Evaluation result: C) As with evaluation result A, measurements were taken after preparing multiple samples with different Gr ratios, Gr orientation rates, and thicknesses of the first material that constitutes the first layer. The thickness of the completed laminate was 0.8 mm. The composition and measurement results of each sample are shown in Table 3. The measurement items shown in Table 3 are the same as those in Table 1.

[0075] [Table 3]

[0076] The performance required for the laminate to become a heat sink is judged to be good based on the criteria that the end temperature difference is 50°C or less and the linear expansion coefficient within the layer is 8 ppm / K or less. As shown in Table 3, Experimental Examples C3 to C5, C8 and C9 are judged to be good.

[0077] Experimental example C1 is the measurement result of a sample that does not contain Gr in the first layer. Since it does not contain Gr, it does not meet the above criteria. Experimental examples C2 to C6 are the measurement results of samples with the same thickness of the first layer but different Gr ratios and Gr orientation rates. Since a Gr ratio of 2.6 Vol% does not meet the criteria, it is considered that a Gr ratio of 3 Vol% or more is necessary. The Gr ratio is preferably 5 Vol% or more. Furthermore, from a comparison of experimental examples C5 and C6, it is determined that the upper limit of the Gr ratio is 16 Vol% or less, preferably 15 Vol% or less. Furthermore, taking into account experimental examples C5 and C6, it is preferable that the Gr orientation rate is 66% or more.

[0078] Experimental examples C4 and C7 to C9 are the measurement results for samples with the same Gr ratio and Gr orientation rate but different thicknesses. From these results, it is determined that the thickness of the first layer of the heat sink should be 0.1 mm or more.

[0079] Furthermore, the higher the proportion of copper in the entire heat sink, the higher the thermal conductivity in the thickness direction, making it more preferable for the heat sink. In that respect, all of the samples judged to be preferable above had a good thermal conductivity in the thickness direction of 250 W / m K or more.

[0080] Example D A laminate was produced in the same manner as in Example A, except that a tungsten-copper (W-Cu) composite was used as the second material.

[0081] (Preparation of Tungsten Copper Complex) Granular tungsten powder (C50, manufactured by A.L.M.T. Co., Ltd.) with an average particle size of 3 μm was filled into a sintering vessel to a thickness of 1 mm so that the powder was 65% by volume. This was sintered in a hydrogen atmosphere at a temperature of 2200°C for 1 hour to obtain a porous body. Molten copper was poured into this porous body to impregnate it. After impregnation, the material was polished to a thickness of 0.15 mm to produce a tungsten-copper composite.

[0082] (Evaluation result: D) As with evaluation result A, measurements were taken by preparing multiple samples with different Gr ratios, Gr orientation rates, and thicknesses of the first material that constitutes the first layer. The thickness of the completed laminate was 1 mm or 1.1 mm. The composition and measurement results of each sample are shown in Table 4. The measurement items shown in Table 4 are the same as those in Table 1.

[0083] [Table 4]

[0084] The performance required for the laminate to become a heat sink is a temperature difference at the ends of 50°C or less, and a linear expansion coefficient within the layer of 8 ppm / K or less. As shown in Table 4, experimental examples D3 to D5, D8, and D9 are judged to be good.

[0085] Experimental example D1 is the measurement result of a sample that does not contain Gr in the first layer. Since it does not contain Gr, it does not meet the above criteria. Experimental examples D2 to D6 are the measurement results of samples with the same thickness of the first layer but different Gr ratios and Gr orientation rates. Since a Gr ratio of 2.5 Vol% does not meet the criteria, it is considered that a Gr ratio of 3 Vol% or more is necessary. The Gr ratio is preferably 5 Vol% or more. Furthermore, from a comparison of experimental examples D5 and D6, it is determined that the upper limit of the Gr ratio is 16 Vol% or less, preferably 15 Vol% or less. Furthermore, taking into account experimental examples D5 and D6, it is preferable that the Gr orientation rate is 66% or more.

[0086] Experimental examples D4 and D7 to D10 are the measurement results for samples with the same Gr ratio and Gr orientation rate but different thicknesses. From these results, it is determined that the thickness of the first layer of the heat sink is suitable to be 0.15 mm or more and 0.30 mm or less.

[0087] Furthermore, the higher the proportion of copper in the entire heat sink, the higher the thermal conductivity in the thickness direction, making it more preferable for the heat sink. In that respect, all of the samples judged to be preferable above had a good thermal conductivity in the thickness direction of 250 W / m K or more.

[0088] Example E A laminate was produced in the same manner as in Example A, except that a tungsten-molybdenum-copper (W-Mo-Cu) composite was used as the second material.

[0089] (Preparation of Tungsten Molybdenum Copper Complex) Granular molybdenum powder with an average particle size of 5 μm (TMO60, A.L.M.T. Corporation) and granular tungsten powder with an average particle size of 3 μm (C50, A.L.M.T. Corporation) were prepared. These materials were filled into a sintering vessel to a thickness of 1 mm so that the molybdenum content was 35 volume % and the tungsten content was 35 volume %. This was sintered in a hydrogen atmosphere at a temperature of 2200°C for 1 hour to obtain a porous body. Molten copper was poured into this porous body to impregnate it. The impregnated material was then polished to a thickness of 0.15 mm to obtain a tungsten-molybdenum-copper composite.

[0090] (Evaluation result: E) As with evaluation result A, measurements were taken by preparing multiple samples with different Gr ratios, Gr orientation rates, and thicknesses of the first material that constitutes the first layer. The thickness of the completed laminate was 1 mm or 1.1 mm. The composition and measurement results of each sample are shown in Table 5. The measurement items shown in Table 5 are the same as those in Table 1.

[0091] [Table 5]

[0092] The performance required for the laminate to become a heat sink is a temperature difference at the ends of 50°C or less, and a linear expansion coefficient within the layer of 8 ppm / K or less. As shown in Table 5, experimental examples E3 to E5, E8, and E9 are judged to be good.

[0093] Experimental example E1 is the measurement result of a sample that does not contain Gr in the first layer. Since it does not contain Gr, it does not meet the above criteria. Experimental examples E2 to E6 are the measurement results of samples with the same thickness of the first layer but different Gr ratios and Gr orientation rates. Since a Gr ratio of 2.5 Vol% does not meet the criteria, it is considered that a Gr ratio of 3 Vol% or more is necessary. The Gr ratio is preferably 5 Vol% or more. Furthermore, from a comparison of experimental examples E5 and E6, it is determined that the upper limit of the Gr ratio is 16 Vol% or less, preferably 15 Vol% or less. Furthermore, taking into account experimental examples E5 and E6, it is preferable that the Gr orientation rate is 66% or more.

[0094] Experimental examples E4 and E7 to E10 are the measurement results for samples with the same Gr ratio and Gr orientation rate but different thicknesses. From these results, it is determined that the thickness of the first layer of the heat sink is suitable to be 0.15 mm or more and 0.30 mm or less.

[0095] Furthermore, the higher the proportion of copper in the entire heat sink, the higher the thermal conductivity in the thickness direction, making it more preferable for the heat sink. In that respect, all of the samples judged to be preferable above had a good thermal conductivity in the thickness direction of 250 W / m K or more.

[0096] Example F In order to confirm the difference in performance due to differences in the overall thickness of the laminate, a laminate was produced in which the thickness of each layer was varied in the same manner as in Example A, using a molybdenum plate as the second material.

[0097] (Evaluation result: F) A number of samples with different thicknesses were prepared with the same Gr ratio and Gr orientation rate of the first material constituting the first layer. Experimental examples F1 to F3 shown in Table 6 are data for a completed laminate with a thickness of 0.8 mm. Experimental examples F4 to F8 shown in Table 6 are data for a completed laminate with a thickness of 2 mm. Moreover, experimental examples A5 to A7, A11, and A12 in Table 1 are data for a thickness of 1 mm. The measurement items shown in Table 6 are the same as those in Table 1.

[0098] [Table 6]

[0099] The performance required for the laminate that will become a heat sink is judged to be good based on the criteria that the end temperature difference is 50°C or less and the linear expansion coefficient within the layer is 8 ppm / K or less.

[0100] When the thickness of the laminate is 1 mm, experimental examples A5 to A7 are judged to be good. When the thickness of the laminate is 0.8 mm, experimental examples F2 and F3 are judged to be good. When the thickness of the laminate is 2 mm, experimental examples F5 to F7 are judged to be good. As described above, even when the overall thickness of the laminate is different, it is found that the thickness of the first material, which is the first layer, is suitable to be 0.15 mm or more and 0.30 mm or less.

[0101] Example G In order to confirm the difference in performance due to the difference in the number of layers in the laminate, an experiment was conducted using a molybdenum plate as the second material.

[0102] (Manufacture of heat sinks) The heat sink having three layers in total has the structure shown in FIG. 5A. The first and second materials were prepared in the same manner as in the manufacturing method of Example A, and a laminate was formed by hot pressing under the same conditions as in Example A. The heat sink having five layers in total is the laminate used in Example A. The heat sink having seven layers in total has the structure shown in FIG. 5B. The first, second and third materials were prepared in the same manner as in the manufacturing method of Example A, and a laminate was formed by hot pressing under the same conditions as in Example A. The heat sink having nine layers in total is made by adding layers of the second and third materials to the seven-layer structure of FIG. 5B, not shown, to make a total of nine layers. The preparation of the first, second and third materials, and the method of forming the laminate are the same as in Example A.

[0103] (Evaluation result G) Experimental examples G1 to G9 in Table 7 show the configurations and evaluation results of a laminate with three layers in total. Experimental examples G10 to G17 in Table 7 show the configurations and evaluation results of a laminate with seven layers in total. Experimental examples G18 to G24 in Table 7 show the configurations and evaluation results of a laminate with nine layers in total. The configurations and evaluation results of a laminate with five layers in total are as shown in Table 1.

[0104] [Table 7]

[0105] The performance required for the laminate to be a heat sink is judged to be good based on the criteria that the end temperature difference is 50°C or less and the linear expansion coefficient within the layer is 8 ppm / K or less. Referring to Tables 1 and 7, comparing the measurement results of samples with the same thickness of the first layer but different Gr ratios and Gr orientation rates, regardless of the total number of layers, the Gr ratio is good when it is 3 Vol% or more and 16 Vol% or less. The Gr ratio is more preferably 5 Vol% or more and 15 Vol% or less. The Gr orientation rate is preferably 66% or more. Also, referring to the measurement results of samples with the same Gr ratio and Gr orientation rate but different thicknesses, the thickness of the first layer is preferably more than 0.1 mm and less than 0.35 mm. The range of the thickness of the first layer in which good results can be confirmed regardless of the number of layers is 0.15 mm or more and 0.30 mm or less.

[0106] It should be noted that the embodiments disclosed herein are illustrative in all respects and should not be considered as limiting. The present invention is not limited to these examples, but is indicated by the scope of the claims, and is intended to include all modifications within the scope of the claims and the meaning equivalent to the claims. [Explanation of symbols]

[0107] 1 Heat sink 2 surface 3 Back side 10 1st material 20 Second material 30 Third material 101 1st layer 102 2nd layer 103 3rd layer 104 4th layer 105 5th layer 11 Metal phase 12 Addition phase 50 Semiconductor Package 51 Terminal 52 Case material 53 Semiconductor elements 60 Heating element 70 Aluminum Fin

Claims

1. A heat sink having a structure in which three or more layers are laminated, a first layer which is at least one of the two outermost layers in a thickness direction of the laminated structure; the first layer being composed of a first material; the first material is a material including a metal phase mainly composed of copper and an additive phase mainly composed of graphite; The volume ratio of the additive phase to the entire first material is 3 vol% or more and 16 vol% or less, The thickness of the first layer is greater than 0.1 mm and less than 0.35 mm; A value obtained by subtracting the thermal conductivity of the first layer in the thickness direction from the thermal conductivity of the first layer in a plane direction perpendicular to the thickness direction is 60 W / m·K or more. Heat sink.

2. A heat sink having a structure in which three or more layers are laminated, a first layer which is at least one of the two outermost layers in a thickness direction of the laminated structure; The thickness of the first layer is greater than 0.1 mm and less than 0.35 mm; the first layer being composed of a first material; the first material is a material including a metal phase mainly composed of copper and an additive phase mainly composed of graphite; The volume ratio of the additive phase to the entire first material is 3 vol% or more and 16 vol% or less, the additive phase is dispersed as a plurality of particles in the metal phase, the plurality of particles each have an anisotropic shape having a longitudinal direction; the number of the particles having an angle of 20 degrees or less between the longitudinal direction and a plane direction perpendicular to the thickness direction of the first layer accounts for 66% or more of the total number of the plurality of particles; Heat sink.

3. The first layer has a thermal conductivity in the thickness direction of 300 W / m·K or more; The linear expansion coefficient of the first layer in the plane direction when the temperature is changed from room temperature to 300° C. is 17.5 ppm / K or less. The heat sink according to claim 1 or 2.

4. a second layer in contact with the first layer; The second layer has a thermal conductivity in the thickness direction of 140 W / m K or more, The linear expansion coefficient of the second layer in the plane direction when the temperature is changed from room temperature to 300° C. is 8.0 ppm / K or less. The heat sink according to any one of claims 1 to 3.

5. the second layer being composed of a second material including molybdenum or tungsten; The heat sink according to claim 4.

6. The laminated layers are three layers, both of the outermost layers are the first layer, The layer between the two outermost layers is the second layer. The heat sink according to claim 4 or 5.

7. The laminated layers are an odd number of layers of 5 or more, both of the outermost layers are the first layer, a pair of layers in contact with each of the outermost layers are the second layers, a third layer in contact with a surface of the pair of second layers opposite to a surface in contact with the first layer is made of copper or a copper alloy; The heat sink according to claim 4 or 5.

8. A heat sink according to any one of claims 1 to 7; a semiconductor element disposed on a surface of the first layer. Semiconductor package.

Citation Information

Patent Citations

  • Radiator plate and manufacturing method for the same

    JP2019096654A

  • Heat-dissipating structure and method for fabricating the same

    US20110083835A1

  • Heat-dissipating plate for high-power element

    US20180328677A1

  • Metal-graphite composite material having high thermal conductivity and method for producing the same

    WO2009051094A1

  • Substrate for power module, and power module

    WO2011096542A1